Biodegradation of Unpretreated Low-Density Polyethylene (LDPE) by Stenotrophomonas sp. and Achromobacter sp., Isolated From Waste Dumpsite and Drilling Fluid - Dey, Anindya Sundar; Bose, Himadri; Mohapatra, Balaram; Sar, Pinaki (Frontiers in Microbiology, 2020)
Exploring the catabolic repertoire of natural bacteria for biodegradation of plastics is one of the priority areas of biotechnology research. Low Density Polyethylene (LDPE) is recalcitrant and poses serious threats to our environment. The present study explored the LDPE biodegradation potential of aerobic bacteria enriched from municipal waste dumpsite and bentonite based drilling fluids from a deep subsurface drilling operation. Considerable bacterial growth coupled with significant weight loss of the LDPE beads (~ 8%), change in pH to acidic condition and biofilm cell growth around the beads (CFU count 105-106/cm2) were noted for two samples (P and DF2). The enriched microbial consortia thus obtained displayed high (65-90%) cell surface hydrophobicity, confirming their potential towards LDPE adhesion as well as biofilm formation. Two LDPE degrading bacterial strains affiliated to Stenotrophomonas sp. and Achromobacter sp. were isolated as pure culture from P and DF2 enrichments. 16S rRNA gene sequences of these isolates indicated their taxonomic novelty. Further biodegradation studies provided strong evidence towards the LDPE metabolizing ability of these two organisms. Atomic Fore Microscopy (AFM) and Scanning Electron Microscopy (SEM) revealed considerable damage (in terms of formation of cracks, grooves etc.) on the micrometric surface of the LDPE film. Analysis of the average roughness (Ra), root mean square roughness (Rq), average height (Rz), maximum peak height (Rp), and maximum valley depth (Rv) (nano-roughness parameters) through AFM indicated 2-3 fold increase in nano-roughness of the LDPE film. FTIR analysis suggested incorporation of alkoxy (1000-1090 cm-1), acyl (1220 cm-1), nitro (1500-1600 cm-1), carbonyl (1720 cm-1) groups into the carbon backbone, formation of N-O stretching (1360 cm-1) and chain scission (905 cm-1) in the microbially treated LDPEs. Increase in carbonyl index (15-20 fold), double bond index (1.5-2 fold) and terminal double bond index (30-40 fold) confirmed that biodegraded LDPEs had undergone oxidation, vinylene formation and chain scission. The data suggested that oxidation and dehydrogenation could be the key steps allowing formation of low molecular weight products suitable for their further mineralization by the test bacteria. The study highlighted LDPE degrading ability of natural bacteria and provided the opportunity for their development in plastic remediation process.